"Am I really alive?": Understanding the role of homophobia, biphobia and transphobia in young LGBT+ people's suicidal distress. (April 2022) - Marzetti, Hazel; McDaid, Lisa; O'Connor, Rory
Abstract: Suicide is the fourth leading cause of death amongst young people aged 15–29 globally and amongst this young population, lesbian, gay, bisexual and trans (LGBT+) young people have higher rates of suicidal thoughts and attempts than their cisgender (non-trans), heterosexual peers. However, despite well-established knowledge on the existence of this health inequality, in the UK there has been a paucity of research exploring why this disparity exists, and this is particularly the case in Scotland. This paper aims to address this gap, reporting on the first study specifically seeking to understand LGBT+ young people's suicidal thoughts and attempts in Scotland. We used a qualitative methodology to explore how young people with lived experience of suicidal distress make sense of the relationship between homophobia, biphobia and transphobia, and suicidal thoughts and attempts. We undertook in-depth, narrative interviews with twenty-four LGBT+ people aged 16–24, and analysed them using reflexive thematic analysis. Drawing on this analysis, we argue that suicide can be understood as a response to stigma, discrimination and harassment, made possible by a cultural climate that positions LGBT+ people as different or other, reinforcing norms regarding gender conformity and sexuality. We suggest in turn, that this cultural climate provides fertile ground from which more explicit acts of homophobia, biphobia and transphobia, such as bullying and family rejection are able to grow. In response to this, LGBT+ young people could begin to experience senses of entrapment, rejection and isolation, to which suicidal thoughts and attempts can be understood as responses. Consequently, we propose that these stigma experiences must be taken seriously and tackled directly in order to reduce LGBT + suicide in the future. Highlights: Queerphobia can act as a central contributor to LGBT + youths' suicidal distress. Queerphobia is made possible by socially accepted norms of gender and sexuality. Rejection of youths' gender or sexuality can be understood as rejection of the whole self. Suicide can be seen as a way to escape or embody rejection from others. To prevent LGBT + suicide, prevention strategies must tackle queerphobia.